# If cotx(1 + sinx) = 4m and cotx(1 – sinx) = 4n, prove that (m2 – n2)2 = mn.

Given 4m = cotx (1+ sinx) and 4n = cotx (1 – sinx)

Multiplying both equations, we get

16mn = cot2x (1 – sin2x)

We know that 1 – sin2x = cos2x

16mn = cot2x cos2x … (1)

Squaring the given equations and then subtracting,

16m2 = cot2x (1+ sinx)2 and 16n2 = cot2x (1 – sinx)2

16m2 – 16n2 = cot2x (4 sinx) Squaring both sides,  … (2)

From (1) and (2),

(m2 – n2) = mn

Hence proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Conditional IdentitiesFREE Class  Trigonometric Functions - 0152 mins  Trigonometric Functions - 0568 mins  Trigonometric Functions - 0658 mins  Trigonometric Functions - 0366 mins  Trigonometric Series45 mins  Interactive Quiz on trigonometric ratios & identities73 mins  Trigonometric Functions - 0268 mins  Trigonometric Functions - 0466 mins  Trigonometric Functions - 0865 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 